Oxytocin signaling in the ventral tegmental area mediates social isolation-induced craving for social interaction - Hsin-Tzu Chang; Kuan-Hsiang Cheng; Yu-Chieh Hung; Kuei-Sen Hsu (Journal of Biomedical Science)
Abstract Background Social interaction is crucial for mental health across animal species. Social experiences, especially in early-life stages, strongly influence brain function and social behavior later in life. Acute social isolation (SI) increases motivation to seek social interaction, but little is known about its underlying neuronal and circuitry mechanisms. Here, we focus on oxytocin signaling in the ventral tegmental area (VTA), a vital node of the brain's reward network, as a potential mechanism for SI-induced craving for social interaction. Methods Adolescent (4-week-old) or adult (14-week-old) male C57BL/6J mice underwent a 1-week SI. Free interaction, object exploration, three-chamber social approach, and habituation tests were used to assess social and non-social behavior changes. Viral vectors were used to decipher the underlying neural circuitry, and chemogenetic techniques were applied to modify neuronal activity. Results We found that in male C57BL/6J mice, SI during adolescence, but not adulthood, leads to increased craving for social interaction and object exploration, accompanied by impaired social habituation, social novelty preference, and social recognition memory (SRM). SI-induced craving for social interaction and SRM deficit is still observed upon regrouping. Through cell-type-specific manipulations with designer receptors exclusively activated by designer drugs (DREADD), we show that oxytocin neurons in the paraventricular nucleus of the hypothalamus (PVN) are crucial for SI-induced social behavior changes. Chemogenetic activation of PVN oxytocin neurons recapitulates social behavior changes observed in SI mice, whereas chemogenetic inhibition of oxytocin neurons prevents social behavior changes caused by SI. Moreover, we found that dopaminergic neurons in the VTA mediate SI-induced craving for social interaction through their projections to the medial prefrontal cortex (mPFC), but not to the nucleus accumbens. Injection of a specific oxytocin receptor antagonist L368,899 into the VTA or chemical lesions of dopaminergic axon terminals in the mPFC with local application of 6-hydroxydopamine ameliorates SI-induced social behavior changes. Conclusions These findings suggest that adolescent SI has enduring effects on social behaviors in male mice through an oxytocinergic modulation of the VTA-to-mPFC dopaminergic circuit activity.